An Assessment of Accommodation Strategies for Coastal Adaptation in Cape Town, South Africa, in Response to Climate Change - Faasen, Petronella (Stellenbosch : Stellenbosch University, 2014)
Thesis (MScEng)--Stellenbosch University, 2014.